Aplicación de nanotecnología para remediación de suelos contaminados con hidrocarburos (2022)
In this document, a descriptive investigation was carried out on the different methods that exist to apply nanotechnology in soils contaminated by the oil industry, because the latter is one of the most criticized worldwide for its contribution to the damage of flora and fauna. the wildlife. To reach the main objective of this research, a description of the contamination process due to hydrocarbons was carried out, to later mention the different synthesis techniques which are important for the approach of each nanoparticle and finally the different methods that were used were shown. have been implemented in the last 10 years using nanotechnology as the main actor to help remediate soils contaminated by hydrocarbons, which helped through SWOT analysis to select the best method, which is nanoemulsions with oil of orange peel leaving removal results of 97.5%, it was shown that it is a method with rapid responses, compared to the micro-nanobubbles technique which leaves a contaminant removal value of only 49%, being This is the least effective in the elimination of hydrocarbons in the soil. However, the application method of nanocatalysts, as well as that of nanoemulsions, left high standards in terms of removal results, showing values ​​greater than 95% in short times once the technique is developed.